Carcinoid tumours of the lung and the 'PEPPS' approach: evaluation of preoperative bronchoscopic tumour debulking as preparation for subsequent parenchyma-sparing surgery. Issue 1 (15th July 2015) - Neuberger, Michael; Hapfelmeier, Alexander; Schmidt, Michael; Gesierich, Wolfgang; Reichenberger, Frank; Morresi-Hauf, Alicia; Hatz, Rudolf A; Lindner, Michael
Abstract : Background: Preoperative bronchoscopic tumour ablation has been suggested as a beneficial treatment for bronchopulmonary carcinoid tumours, although data regarding its effects and long-term outcome are lacking. Methods: In our case-matched cohort study with 208 patients with bronchopulmonary carcinoid tumours we investigated the role of preoperative bronchoscopic interventions before subsequent surgery and analysed the safety of this Procedure of Endobronchial Preparation for Parenchyma-sparing Surgery (PEPPS) based on metastasis and recurrence rates as well as survival data from 1991 to 2010. The subsequent surgery was classified into parenchyma-sparing procedures and classical lobectomies, bilobectomies and pneumonectomies. Data were obtained from the tumour registry and medical reports. Outcomes were the frequency of parenchyma-sparing surgery after bronchoscopic treatment as well as rates of metastasis, recurrence and survival. Results: 132 of 208 carcinoids were located centrally. Among them, 77 patients could be recanalised preoperatively. After bronchoscopic preparation, the rate of subsequent parenchyma-sparing surgery methods was higher (p=0.021). The effect was measured by the number of segments removed. The 10-year survival rate was 89% (typical carcinoids) and 68% (atypical carcinoids), respectively. After applying PEPPS, long-term survival was slightly higher (p=0.23). Metastasis and recurrence rates showed no relevant differences between the bronchoscopically treated or non-treated groups, or between the two types of surgery classes or between the PEPPS and non-PEPPS groups. Conclusions: After preoperative bronchoscopic treatment, parenchyma-sparing surgery techniques can be applied more frequently. Furthermore, we detected no negative effects after PEPPS based on metastasis, recurrence and survival rates.